Description of the physical activity promotion programs funded by the Brazilian Ministry of Health - Tales Amorim; Alan Knuth; Danielle Cruz; Deborah Malta; Rodrigo Reis; Pedro Hallal (Revista Brasileira de Atividade Física e Saúde)
As a means to operationalize the National Health Promotion Policy, the Brazilian Ministry of Health funded cities for the development of local health promotion interventions from 2005 to 2009. Out of 1,374 interventions funded in this period, approximately 3/4 developed physical activity promotion strategies. The aim of this article is to describe these interventions. We interviewed those who are responsible for these interventions in 748 cities in Brazil. The Midwest region was the one with the highest proportion of cities being funded (17.8%); 72.3% of the interventions take place in small cities, i.e. those with fewer than 30,000 inhabitants. Communication, education and information strategies were the mostly frequently reported, followed by behavioral and social strategies. Only 8.2% of the interventions achieve more than 500 people. Most interventions (76.9%) focused on older adults, and 59.2% of them were designed for hypertensive and diabetic patients. Oriented walking was the most prevalent offered activity (80.6%), followed by gym classes (78.5%). Most interventions used parks or squares (55.6%) or sports courts (52%). Radio was the most frequent media strategy used (59.8%) to divulgate the interventions. Lack of adequate physical structure and personnel were the main barriers faced by the interventions (30.3%), followed by bureaucracy at obtaining and using the funding (25.1%). Physical education teachers were present in 72.3% of the interventions. The low proportion of funded cities in the North region, the lack of interventions using environmental and policy strategies, inadequate infrastructure and insufficient personnel are key areas in which interventions can improve in order to be more successful.